El poeta Belano alecciona a los maestros - Báez Meza, Marcelo (2021)
This article focuses on Roberto Bolaño’s critical attitude towards the figure of the master. Two characters stand out in the spotlight of Bolaño’s irony in the novel Los detectives salvajes: Miguel Donoso Pareja and Octavio Paz. The former appears under the name of Gustavo Pardo and the latter under his real name. This iconoclastic attitude is reflected in the subversion as part of the ethic of visceral realism and recalls in a certain way the spirit of the Tzántzicos.